A methodology for transactional risk assessment and decision making in e-business interactions - Hussain, Omar; Dillon, Tharam S.; Chang, Elizabeth; Hussain, Farookh Khadeer (IEEE, 2009)
The development and advancement of technologies have enabled users to complete their tasks efficiently. They have also provided them with various options and alternatives to complete and achieve their tasks. In such an environment, it is imperative for a user to make informed decisions that would ensure that its aims or objectives are achieved and its interaction experience is maximized. In the literature, various approaches for decision making have been proposed. But among those approaches, the notion of risk has been considerably ignored in the domain of e-business, despite its having been acknowledged as an important concept related to decision-making in any domain. In this paper, we propose a methodology by which users in an e-business domain can assess and analyze the level of transactional risk in the domain of e-business and then take it into consideration when making an informed interaction-based decision.